Analisis Faktor-Faktor yang Mempengaruhi Mahasiswa Akuntansi di Kota Malang Atas Pilihan Karir Sebagai Akuntan Publik - Sofiah, Sofiah; Junaidi, Junaidi; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This study aims to determine the effect of self-efficacy, financial rewards and job market considerations on the career choices of accounting students as public accountants. The population in this study is students of accounting study programs, faculty of economics and business, Islamic University of Malang, Maulana Malik Ibrahim State Islamic University of Malang and Brawijaya University. The method of this research approach is the purposive sampling method, which uses certain criteria in determining samples using questionnaires and using SPSS. The results of this study simultaneously and partially show that variables of self-efficacy, financial rewards, and job market considerations have a positive and significant effect on the career choices of accounting students as public accountants.    Keywords: Self-efficacy, financial reward, job market considerations, career choice, public accountant